On scaling of proton- boron fusion power in a nanosecond vacuum discharge - Kurilenkov, Yu. K.; Andreev, S. N. (Frontiers in Physics, 2024)
In this paper, we present the results of further PiC simulations in the full electromagnetic code of the processes leading to the proton-boron reactions in a single device for plasma confinement, based on miniature nanosecond vacuum discharge (NVD) in a cylindrical geometry. In particular, we present and discuss in more detail the α particle output for the real electrodes geometry used in the first aneutronic proton–boron fusion experiments with NVD. It follows from them that the total yield of α particles was accumulated in the initial experiments due to only single head-on converging of protons and boron ions accelerated in a very narrow potential well to the discharge axis. Further, in search of the ways for optimizing of proton–boron fusion in NVD, we study the scaling of fusion power depending on the size of the virtual cathode (or the inner radius of the anode space). The results of the PiC simulations by KARAT code show that the number of the proton-boron reactions at anode space of NVD increases with the anode volume grow, and the α particles output turns out to be proportional to the value of anode radius in the range RA ≈ 0.1–0.5 cm. However, the number of proton-boron reactions reaches some saturation under RA growing at the fixed time of high voltage applied and value of the energy input. In general, the formation of a more voluminous potential well (wider in radius and extended along the discharge axis), with well–defined oscillations of protons and boron ions in it, provides a noticeable increase in the output of α particles.